Sobre la causalidad de los gastos deducibles para efectos del impuesto a la renta. Un enfoque empresarial - Santiváñez Guarniz, Juan (2009)
The fiscal charges of the income tax state that if we want to consider an expense as deductible it must fulfill the causality principle, apart from that, they state rules that expenses are necessary to generate income and fulfill the criterion of reasonable expenses, majority among others.Showing that an expense is a necessity is a complicated task that in many cases will force — the person to determine that necessity — to examine internal aspects of the company, as business strategies, internal policies, etc. Apart from the analytical complexity of these topics, there will be the subjective aspect from the point of view of the outside observer.This article pretends to show the difficulty to decide if an expense is necessary or not, through the analysis of a real case where the tax system denies expenses of a taxpayer because they were not considered necessary for that kind of business.